2016
DOI: 10.1007/7854_2016_24
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Stimulus Properties of Phytocannabinoids, Endocannabinoids, and Synthetic Cannabinoids

Abstract: Psychoactive cannabinoids from the marijuana plant (phytocannabinoids), from the body (endocannabinoids), and from the research lab (synthetic cannabinoids) produce their discriminative stimulus effects by stimulation of CB receptors in the brain. Early discrimination work with phytocannabinoids confirmed that Δ-tetrahydrocannabinol (Δ-THC) is the primary psychoactive constituent of the marijuana plant, with more recent work focusing on characterization of the contribution of the major endocannabinoids, ananda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 126 publications
3
7
0
Order By: Relevance
“…Consistent with previous results, THC served as a robust discriminative stimulus in male mice (present study; Gamage et al, 2018;Wiley et al, 2015) and rats (Wiley et al, 2014a;Wiley et al, 1995). The present study also is one of the few reports of THC's discriminative stimulus effects in female rodents (Wiley et al, 2018;Wiley et al, 2011;Winsauer et al, 2012). In mice, use of the same THC training dose (5.6 mg/kg) was effective in both sexes (as reported previously; Wiley et al, 2011), and potency for producing responding on the THC-associated aperture was similar, although overall response rates were lower at baseline and across all THC doses in females.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous results, THC served as a robust discriminative stimulus in male mice (present study; Gamage et al, 2018;Wiley et al, 2015) and rats (Wiley et al, 2014a;Wiley et al, 1995). The present study also is one of the few reports of THC's discriminative stimulus effects in female rodents (Wiley et al, 2018;Wiley et al, 2011;Winsauer et al, 2012). In mice, use of the same THC training dose (5.6 mg/kg) was effective in both sexes (as reported previously; Wiley et al, 2011), and potency for producing responding on the THC-associated aperture was similar, although overall response rates were lower at baseline and across all THC doses in females.…”
Section: Discussionsupporting
confidence: 93%
“…In vivo, synthetic cannabinoids produce a profile of pharmacological effects in rodents that is characteristic of psychoactive cannabinoids such as THC: suppression of locomotor activity, antinociception, hypothermia and catalepsy (Wiley et al, 1998;Wiley et al, 2014b;Wiley et al, 2017b). They also produce THC-like effects in THC drug discrimination (reviewed in Wiley et al, 2018), a pharmacologically selective animal model of cannabis intoxication (Balster and Prescott, 1992). With only few exceptions (Wiley et al, 2017a;Wiley et al, 2011;Winsauer et al, 2012), the bulk of this research has been conducted in male rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, all three compounds fully substituted for THC in rats of both sexes, as has been reported previously in THC-discriminating male rats tested with a variety of synthetic cannabinoids (Gatch and Forster, 2014; Wiley et al, 2016). Further, they were more potent than THC and were considerably more so for males than for females.…”
Section: 0 Discussionsupporting
confidence: 77%
“…Previous studies have reported that MAGL inhibitors fully substitute for CP55,940 and for the dual FAAH-MAGL inhibitor SA-57, though they only partially substitute for THC (Hruba et al, 2015; Ignatowska-Jankowska et al, 2014; Long et al, 2009b; Owens et al, 2016; Vann et al, 2012; Wiley et al, 2016, 2011). The present results extend these findings to show that the selective MAGL inhibitor MJN110 serves as a training drug in the drug discrimination paradigm.…”
Section: 1 Discussionismentioning
confidence: 99%
“…Full substitution for MJN110 by the high efficacy CB 1 receptor agonist CP55,940, combined with dose-dependent blockade of MJN110's discriminative stimulus effects by the CB 1 receptor antagonist rimonabant, support the inference that CB 1 receptors mediate the MJN110 discriminative stimulus. Furthermore, MAGL substitution exhibits selectivity, as the MAGL inhibitor JZL184 and the dual FAAH-MAGL inhibitor SA-57 fully substitute and cross-substitute (Hruba et al, 2015; Owens et al, 2016; Wiley et al, 2016, 2011), whereas the FAAH inhibitor PF-3845, the ABHD6 inhibitor KT182, and three noncannabinoid drugs (i.e., valdecoxib, nicotine, and diazepam) do not elicit full substitution for MJN110.…”
Section: 1 Discussionismentioning
confidence: 99%